The Impact of Labor, Investment, and Human Development Index on Economic Growth: A Study of East Kalimantan Province - Febrian Alexander Nababan; Armelly Armelly (UNIVED Press, 2024)
This study aims to examine the factors affecting the economic growth of East Kalimantan province from 2017 – 2021.The analysis method used is regression panel data with dependent variables of economic growth and independent variables, namely labor, human development index, and investment with the best model is using Fixed effect mode (FEM).The results revealed that the human development and labor index obtained a significant positive value with a coefficient value which is also positive for economic growth which can be concluded to provide an increase in the amount of GDP, investment in economic growth has a significant effect and the value of the coefficient obtained is negative.